Corpus der minoischen und mykenischen Siegel: CMS - Anastasiadou, Maria (Institut für Klassische Archäologie, 2017)
The Corpus der minoischen und mykenischen Siegel (CMS) is a long-term project aiming at the systematic documentation and publication of all known Aegean seals and sealings in a consistent manner.